Hierarchical-ring application layer multicast model based on diff-services - XU Jian-zhen1; LIANG Ke-hui1; ZHANG Fu-yan2 (Tongxin xuebao)
To improve the efficiency of application layer multicast （ALM）, an hierarchical-ring ALM model based on diff-services （HRM） was presented. In the model, the ring topology was employed to reduce the control overhead. In the data transmission process, the model used push/pull transmission strategy to reduce transmission delay and increase the bandwidth utilization. Simulation results show that the model provides lower end-to-end delay and link stress and control overhead, which is suitable to those larger scale different types ALM applications.